Karakteristik Fisikokimia, Mikrobiologi dan Sensori Yogurt Susu Kambing (Capra aegagrus hircus) diperkaya Sari Kacang Hijau (Vigna radiata): Physicochemical, Microbiological and Sensory Characteristics of Goat Milk (Capra aegagrus hircus) Yogurt with Mungbean (Vigna radiata) Extract Enrichment - Firmansyah, Hardi; Rosmiati, Risti; Saufani, Iza Ayu; Hanifa, Zulfa Nur (Universitas Airlangga, 2025)
Background: Goat milk offers more superior health benefits than cow milk, while mung beans possess high nutrient contents and promote probiotic growth. Enhancing goat milk yogurt with mung bean extract through fermentation can improve product quality and consumer acceptance by mitigating the off-flavors. Objectives: To determine the physicochemical, microbiological, and sensory characteristics of goat milk yogurt with mung bean extract enrichment. Methods: A Completely Randomized Design (CRD) was employed with four different formulation ratios of goat milk and mung bean extract at 100%:0%, 85%:15%, 70%:30%, and 55%:45%. Physicochemical properties, such as pH, acidity, ash, total solids, protein, fat, and total sugar were analyzed. on the total amount of lactic acid bacteria (LAB) was counted as microbiological analysis component. Sensory evaluations were conducted using hedonic and hedonic quality tests. All parameters were analyzed using a one-way ANOVA, and the best formulation ratio was determined using the De Garmo method. Results: pH of the product was 3.96 to 4.12, as acidity increased along with a higher mung bean extract. Ash, protein, fat, and total solids content varied moderately across samples, influencing the nutritional profiles of the yogurt. The amount of LAB peaked at 8.95 Log CFU/ml in the 85%:15% formulation ratio. Sensory evaluations showed the highest score of texture and overall assessments in the 85%:15% formulation ratio by achieving optimal tanginess, sweetness, and texture balance. Conclusions: Enriching goat milk yogurt with mung bean extract can significantly influence the physicochemical, microbiological, and sensory characteristics. The formulation of 85% goat milk and 15% mung bean extract provides the more enhanced nutritional value, probiotic potential, and consumer acceptance.